Promises and Limitations of Nudging in Education - Philip Oreopoulos (Institute of Labor Economics (IZA), 2020)
This article takes stock of where the field of behavioral science applied to education policy seems to be at, which avenues seem promising and which ones seem like dead ends. I present a curated set of studies rather than an exhaustive literature review, categorizing interventions by whether they nudge (keep options intact) or "shove" (restrict choice), and whether they apply a high or low touch (whether they use face-to-face interaction or not). Many recent attempts to test large-scale low touch nudges find precisely estimated null effects, suggesting we should not expect letters, text messages, and online exercises to serve as panaceas for addressing education policy's key challenges. Programs that impose more choice-limiting structure to a youth's routine, like mandated tutoring, or programs that nudge parents, appear more promising.
Keywords: I2; J24; 330; behavioral economics of education; nudge; shove